PENGARUH KEHADIRAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI ROLE MODEL TERHADAP PERILAKU RELIGIUS SISWA DI MAN 2 KARAWANG - Nur Asysyiddah, Ismaya; Achmad Junaedi Sitika; Siti Khulasoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the presence of Islamic Religious Education (PAI) teachers as role models on students' religious behavior at MAN 2 Karawang. Religious education in schools is not only oriented towards knowledge transfer, but also character building and internalization of religious values ​​in daily life. Therefore, teacher role models are an important factor in shaping students' religious behavior. This study used a quantitative approach with a correlational survey method. The research sample consisted of 28 grade XI students selected through a purposive sampling technique. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis used descriptive statistics and simple linear regression. The results showed that the presence of Islamic Religious Education (PAI) teachers was in the moderate category with an average value of 32.21, while students' religious behavior was in the moderate category with an average value of 34.29. The regression test showed a positive relationship with an R value of 0.583 and a coefficient of determination of 34.0%. This confirms that teacher role models have a significant contribution in shaping students' religious behavior. Thus, improving the quality of Islamic Religious Education teachers' role models is a strategic step in strengthening the character of students in the madrasa environment (Akip et al., 2025; Dewangga et al., 2026).